HIGH SPEED TRANSPORT - SUPPORT FOR SUSTAINABLE MOBILITY - Nedeliaková, Eva; Dolinayová, Anna; Čamaj, Juraj (Doprava a spoje, 2008)
This article deals with high speed transport, as support for sustainable mobility, in the world, its present state and perspectives to the future. High speed rail systems play an important role for economic and social development wherever they have been introduced. There are defined facts about network and rolling stock. Technical aspects are very important for the construction of the high speed track. Commercial aspects create inseparable part of high transport existence. Market share is one of the positive indicators, which can be seen in last years. The article describes advantages of high speed transport for society, high transport capacity and respects the environment.